HUBUNGAN TINGKAT PENGETAHUAN KOSMETIKA MODERN TERHADAP PERILAKU PEMILIHAN KOSMETIK PERAWATAN KULIT WAJAH BERMINYAK: Studi Pada Mahasiswa Pendidikan Tata Rias Universitas Negeri Jakarta - Filli, Btari Annisaa; Yulia, Elvyra; Ambarwati, Neneng Siti Silfi (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Knowledge of the types of facial care cosmetics is necessary in maintaining facial health, especially in Indonesia oily skin is a fairly common problem, therefore it takes a good knowledge of the types of facial care cosmetics and how they work on the skin. This study aims to determine the relationship between the level of knowledge of modern facial care cosmetics on the selection behavior of oily facial skin care cosmetics. This research is a quantitative research with survey method. The variables used are independent variables, namely knowledge of modern facial care cosmetics, and dependent variables, namely the behavior of choosing cosmetics, oily facial skin care. This research was conducted at Jakarta State University and was conducted from February to February August 2023. The sampling technique used is a total sampling technique  with a sample of 47 students of Cosmetology Education at Universitas Negeri Jakarta class of 2022. Data collection method through questionnaires and literature studies. Data analysis was carried out in the form of correlation analysis and simple linear regression analysis between knowledge variables about modern cosmetics and behavioral variables of selection of oily facial skin care cosmetics using SPSS 25. The result of this study is that there is a positive correlation between the two variables, the relationship is relatively weak and not statistically significant. Further analysis through a simple linear regression model also revealed that the coefficients for modern facial care cosmetic knowledge variables did not have a significant impact on cosmetic selection behavior. Analysis of the coefficient of determination showed that the model was only able to explain about 4.2% of the variation in the selection behavior of oily facial skin care cosmetics